If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 54 = 16x + -10x Combine like terms: 16x + -10x = 6x 54 = 6x Solving 54 = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 54 + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 54 + -6x = 0 Add '-54' to each side of the equation. 54 + -54 + -6x = 0 + -54 Combine like terms: 54 + -54 = 0 0 + -6x = 0 + -54 -6x = 0 + -54 Combine like terms: 0 + -54 = -54 -6x = -54 Divide each side by '-6'. x = 9 Simplifying x = 9
| m^2+3m-5=5 | | 8-3(x+5)=5+3(2x+4) | | t(t+5)=14 | | 2=x^2-4*x | | 60t^3-200t^2-66t+220= | | 2=x^2-4x | | 2x+2/3+x-2/4=15/2 | | (8n-3)(5n+6)=0 | | -5(10r+2)+3(6r+8)= | | 7h^3-35h^2-42h= | | (b+3)(b-1)=0 | | 20x^3=0 | | x^2+0x=16 | | 5y=3y+10 | | x^2-5x-115=11 | | 5x-4x+10=48 | | 4x-5=8x | | 3-1*x=2x-4 | | 4+17y-1=9y+107-7y | | 4-5(3x-2)+6x=7-(5x+1)+3-5x | | 3y^2+42y+147=0 | | 3(6x-5)-2(4x-12)=9x+12 | | 0*x=x^2-4x | | 7s+19s=52 | | 8/x+3=0 | | 0*x=2x-4 | | W^2=-42-13w | | -3x=x^2-4x | | 5/2y+4y/(y-9)=-9/2 | | -5x=2x-4 | | (-5x)=2x-4 | | -4(2b+1)+(9b-5)=0 |